Radiohalogenation of Organic Compounds: Practical Considerations and Challenges for Molecular Imaging - Sutherland, Andrew (Synthesis, 2019)
In the last few decades, advances in molecular imaging technologies have had a major impact on many aspects of healthcare. In particular, radiohalogenated compounds have been used for non-invasive visualization of human anatomy, for the diagnosis of disease and in drug development programs. As a consequence of these advances, a range of novel synthetic radiochemical methods have been reported that allow more effective and efficient radiohalogenation from a broader range of precursors. In developing new radiochemical methods, special requirements are required to optimize the incorporation of highly radioactive, short-lived, isotopically labelled reagents. This article highlights the key practical considerations and challenges encountered when utilizing the most commonly used radiohalogens in nuclear medicine.1 Introduction2 Synthetic Challenges for Radiohalogenation2.1 Radiofluorination2.2 Radioiodination3 Conclusions and Future Outlook
Keywords: halogenation; radiofluorination; radioiodination; radiochemistry; molecular imaging